PEMIKIRAN EKONOMI ISLAM M. UMER CHAPRA - Inayati, Anindya Aryu (Muhammadiyah University Press, 2013)
M. Umer Chapraâs thought in economics is a blend of traditional sciences,theology and modern economics sciences. His thinking is dominated by macro economicsector because he was widely occupied in the world economy. His thinking are includingthe concept of falah, hayyahtayyibah and Muslims economic challenges, monetary policy,the Islamic financial institutions which is concerned to the central bank and its policies,and the concept of welfare states according to Islam. Like the other Muslim economists,Chapra hammered at moral as the way of reaching fair and healthy economy.The privilegedof M. Umer Chapra thought is the ability to mix and match between the Western economicconcepts with Islamic values. He was awarded as the â success Islamic scholar â. While hisslight shortage is in the attitude of tolerance towards Western financial instruments. Thisattitude is the impact of his understanding of the world economy, that may not be erasedfrom these instruments except gradually and slowly. Although Chapra realizes that theIslamic economic system can deliver socio - economic justice to the world and become asolution for the failure of the capitalist and socialist economic systems.Key words: monetary policy, banking system, welfare state.Â Fokus utama makalah ini adalah membahas pemikiran M. Umer Chapra dalambidang ekonomi. Penulis menemukan pemikiran ekonomi Chapra merupakan perpaduanantara ilmu-ilmu tradisional, ilmu agama dan ilmu ekonomi modern. Pemikirannyadidominasi oleh bidang perekonomian makro karena ia banyak berkecimpung di duniaperekonomian negara. Diantara pemikirannya adalah mengenai konsep falah, hayyahthayyibah, dan tantangan ekonomi umat Islam, kebijakan moneter, lembaga keuangansyariah yang lebih ditekankan kepada bank sentral dan kebijakan-kebijakannya, serta konsepnegara sejahtera menurut Islam. Sebagaimana ekonom muslim lainnya, Chapramengedepankan pentinganya moral bagi jalannya perekonomian yang adil dan sehat.Keistimewaan pemikiran M. Umer Chapra adalah kemampuannya memadu-padankanantara konsep-konsep ekonomi Barat dengan nilai-nilai Islam. Sehingga ia mendapatkangelar sebagai âsarjana Islam yang suksesâ. Sedangkan kekuranganannya terletak pada sikaptolerannya terhadap instrumen-instrumen keuangan Barat. Sikap tersebut merupakan imbasdari pemahamannya mengenai keadaan ekonomi dunia yang tidak mungkin dimurnikandari instrumen-instrumen tersebut kecuali secara bertahap dan perlahan. Meskipun Chapramenyadari bahwa sistem ekonomi Islam dapat mengantarkan kepada keadilan sosio-ekonomidunia dan menjadi solusi bagi kegagalan sistem ekonomi kapitalis dan sosialis.Kata kunci: kebijakan moneter, sistem perbankan, negara sejahtera